Fixing Work, and Moving Beyond It. Issue 1 (February 2023) - Liu, Cathy Yang; Doussard, Marc; Lowe, Nichola
This commentary reviews the challenges facing both U.S. workers and the central place of work in economic development. As the Great Resignation demonstrates, work is not working well for large portions of the population. The authors review the diversification of workers and the diversification of work arrangements in recent decades, noting the immense challenges the system faces. They then shift focus to solutions, beginning with workplace development, or interventions to improve employment and productivity within the workplace. Finally, the authors consider universal public services and other investments that improve economic outcomes by addressing employees' needs beyond work.